(untitled) (Economic Journal of Nepal, 2014)
This article examines the relationship between the gross domestic savings, investment and growth for Nepal using annual time series data for the period of 1974/75 to 2009/10. The study employs the Autoregressive Distributed Lag (ARDL) approach to test for cointegration and Error correction based Granger causality analysis for exploring the causality between the variables. Empirical results show that there exist cointegration between gross domestic savings, investment and gross domestic product when each of these is taken as dependent variable. Granger causality analysis shows that there exists short-run bidirectional causality between investment and gross domestic product as well as between gross domestic savings and investment. Nevertheless, no short-run causality is found between gross domestic savings and gross domestic product. Thus, the policy of accelerating growth by promoting investment works to some extant only since the long-run investment multiplier is below one. The Economic Journal of Nepal, Vol. 34, No. 3, July-September 2011